Evaluación del efecto de dos fertilizantes orgánicos aplicados en diferentes dosis en el cultivo de ají (Capsicum chinense Jacq.) - García Sánchez, Milton Bryan (2022)
The use of agrochemicals constantly and consecutively in the cultivation of chili peppers, in which it limits future productions. Implementing conservative techniques improves several processes in the recovery of the soil microbiota.